Sejarah dan Perkembangan Sistem Bilangan di India - Heby Anggriyani Damanik; Lenni Mariana Harahap (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study discusses the history and development of the number system in India and its influence on the evolution of mathematics worldwide. The Indian number system has evolved since the Indus Valley Civilization and has undergone significant innovations, such as the invention of the number zero by Brahmagupta and the development of the place value system, which forms the basis of the modern decimal number system. This research employs a qualitative method with a library research approach, involving the analysis of various written sources, such as books, academic journals, and historical articles on the Indian number system. The findings indicate that the Indian number system has had a profound impact on the advancement of mathematics, particularly after it was introduced to the Islamic world by scholars such as Al-Khwarizmi, who later disseminated it to Europe, making it the foundation of the numerical system used today. Additionally, the Indian number system contributed to the development of various branches of mathematics, including algebra, calculus, and number theory, and served as the foundation for modern technology, including computers and calculators. Therefore, understanding the history of the Indian number system should be reinforced in mathematics education, accompanied by further research on its applications in contemporary science and technology.